Librarians and their instructional role in the academic library an evaluation - Domingo, Charizze Psalm G.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
The study explores the levels of library instruction performed in academic libraries and the development of competence of academic librarians in delivering instruction. It also examines the roles of librarians as library instructors and the accompanying struggles that comes with library instruction and how to address them. The best thoughts that came from the various interviews led to the examination as to the degree to which academic librarians think of their role in library instruction as teachers. This concept drew a lot of other related topics and issues wherein this paper devoted a large bulk to show the practical outworking of this role. Despite the insistence that came out of the majority of respondents to view this particular function to merely scheduled orientations and walk-in inquiries, it is apparent that the actual dispensing of this task goes beyond the pep talk and routinary discussions of the different sections of the library .
Thesis (Bachelor of Library and Information Science)
Keywords: Library orientation; Library education; Libraries and education